ItemComplex: A Python-based visualization framework for ex-post organization and integration of large language-based data sets - Janson, Karina; Gottfried, Karl; Reis, Olaf; Kornhuber, Johannes; Eichler, Anna; Deuschle, Michael; Banaschewski, Tobias; Nees, Frauke (European Psychiatry, 2025)
Background: Nowadays both researchers and clinicians alike have to deal with increasingly larger datasets, specifically also in the context of mental health data. Sophisticated tools for dataset visualization of information from various item-based instruments, being questionnaire data or data from digital applications or clinical documentations, are still lacking, specifically for an integration at multiple levels and for use in both data organization and appropriate construction for its valid use in subsequent analyses. Methods: Here we introduce ItemComplex, a python-based framework for ex-post visualization of large data sets. The method exploits the comprehensive recognition of instrument alignments and the identification of new content networks and graphs based on item similarities and shared versus differential conceptual bases within and across data and studies. Results: The ItemComplex framework was evaluated using four existing large data set from four different cohort studies and demonstrated successful data visualization across multi-item instruments within and across studies. ItemComplex enables researchers and clinicians to navigate through big data sets reliably, informed and quickly. Moreover, it facilitates the extraction of new insights into construct representations and concept identifications within the data. Conclusions: The ItemComplex app is an efficient tool in the field of big data management and analysis addressing the growing complexity of modern datasets to harness the potential hidden within these extensive collections of information. It is also easily adjustable for individual data sets and user preferences, both in the research and clinical field.
CRIS-Team Scopus Importer:2025-06-13
Keywords: big data; constructs; content networks; data navigation; data structuring; data visualization; items